COAGULASE NEGATIVE STAPHYLOCOCCI AMONG CLINICAL ISOLATES IN A TERTIARY CARE CENTRE - S A SARDAR, M SINGH; S BASIREDDY; S ALI; V KABRA (International Journal of Pharma and Bio Sciences, 2015)
Coagulase negative staphylococci are increasingly being reported as etiological agents in a nosocomial setup. Speciation of CoNS is not routinely done because of the practical difficulties as batteries of tests are needed to identify. Drug resistance is a very common observance among CoNS. Above all formation of biofilm makes these organisms more rigid towards the treatment. In the present study 100 CoNS isolated from various samples were speciated phenotypically, their resistance patterns were observed and the potential for the formation of biofilm in individual species is noted. The predominant species isolated in our study was S.epidermidis(43%). Methicillin resistance was noted in 52% of the total isolates. Biofilm production was detected in 40% of the total isolates.